Foundations of public service e pluribus unum. - Banyan, Margaret; Robinson, Kent S.; Shinn, Craig W.; Green, Richard T. (Routledge, 2022)
Designed to serve as a basic text for introductory courses in public administration, this pioneering work provides students with a clear-eyed understanding of the vital management functions covered in most standard textbooks with two important differences.